Shale gas events in Ain Salah and its role in developing awareness among the youth of the region - ABDELDJALIL SAGUENI (Social Empowerment Journal, 2020)
2015 was a year of social mobility in the city of Ain Salah in the central Algerian Desert, the residents of the region came out against the government's decision to explore for shale gas, the latter, which is a powerful resource that many countries seek to make an alternative to oil and natural gas, but its extraction is difficult and requires harm to the environment and human beings, these demonstrations were characterized by a peaceful nature that expressed the awareness of young people, who often resort to force or violence to achieve gains, but this time they used the mind and mechanisms of dialogue, consultation and persuasion,  In this study, we talked about the movement of shale gas in Ain Salah city and about the important and leadership role of young people at different levels of culture and society, and how this movement affected people's lives with a good eye and beyond.